Pengaruh Reputasi Merek dan Kualitas Layanan Terhadap Minat Beli di Blibli.com - Eugenius Sandy; Donant Alananto Iskandar (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2022)
The purpose of this study is to find out whether there is an influence of Brand Reputation and Service Quality on Buying Interests in Blibli.com This study uses validity tests, reliability tests, multiple linear regression tests, and hypothesis tests both partial and simultaneous with the help of spss version 20 program. The sample was taken by 95 respondents. The research uses quantitative approach with purposive sampling technique method. Data collection is done by disseminating questionnaires using the Likert scale to measure each statement. The results showed that there is a positive and significant influence between price perception and service quality on the decision to purchase electronic products in XYZ stores.